Leray-Schauder type alternatives, complementarity problems and variational inequalities - Isac, George (New York : Springer, 2006)
"This book is the first to discuss complementarity theory and variational inequalities using Leray-Schauder type alternatives. The ideas and method presented in this book may be considered as a starting point for new developments. This book is intended for researchers and advanced graduate students in optimization, applied nonlinear analysis, complementarity theory, the theory of variational inequalities, and operations research."--BOOK JACKET.
1. Preliminary notions -- 2. Complementarity problems and variational inequalities -- 3. Leray-Schauder alternatives -- 4. The origin of the notion of exceptional family of elements -- 5. Leray-Schauder type alternatives : existence theorems -- 6. Infinitesimal exceptional family of elements -- 7. More about the notion of exceptional family of elements -- 8. Exceptional family of elements and variational inequalities.
Includes bibliographic references and index.
hardcover
Keywords: Nonlinear operators; Fixed point theory